1997
DOI: 10.1088/0022-3727/30/11/003
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation spectroscopy of polyethylene terephthalate (PET) films

Abstract: The dielectric properties of biaxially stretched polyethylene terephthalate (PET) films of thickness and 68% degree of crystallinity were investigated by means of dielectric relaxation spectroscopy in the frequency range Hz and the temperature range C. Differencial scanning calorimetry (DSC), in the range C, was employed to investigate the thermal properties of the PET samples. Besides measuring the relaxation associated with the glass transition and the secondary relaxation, special attention has been pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 34 publications
9
76
0
2
Order By: Relevance
“…From the plot of Fig. 7, reasonable values for the dielectric constant were obtained, 21 confirming that the Poole-Frenkel conduction model is appropriate to explain the experimental results with the CC method. This is not surprising since it is well known that the Poole-Frenkel conduction plays an important role in PET polymer.…”
Section: Electric Conduction In Petsupporting
confidence: 66%
See 1 more Smart Citation
“…From the plot of Fig. 7, reasonable values for the dielectric constant were obtained, 21 confirming that the Poole-Frenkel conduction model is appropriate to explain the experimental results with the CC method. This is not surprising since it is well known that the Poole-Frenkel conduction plays an important role in PET polymer.…”
Section: Electric Conduction In Petsupporting
confidence: 66%
“…14 Finally, it was shown that the electric conduction in PET obeys the Poole-Frenkel law in agreement with published data. 21,22 Theoretical models for CC measurements are already available and described in the literature 12 for several cases such as free charge injection and charge injection in the presence of trapping. Such models were originally applied to corona charging measurements under open circuit but they are the same for closed circuit measurements.…”
Section: Discussionmentioning
confidence: 99%
“…These blends are initially immiscible but quickly react and phase structure changes via transesterification in the melt. Whilst the dielectric properties of PET [5,6] have been investigated, PEN has been much less investigated [7]. Ezquerra et al [8] undertook a detailed study into the primary and secondary relaxations of amorphous random copolymer films of PET and PEN.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal, electrical and mechanical properties of polymers are useful for use in technological and biological applications [1][2][3][4][5][6][7]. Thin polymer films obtained by plasma polymerization are generally more biocompatible than conventional biomaterials such as Silastic.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13,21,22]. In addition, there are reports on the dielectric properties of [2,23,24] and on the comparison of their dielectric properties with the structural properties of plasma polymers [25][26][27][28][29]. However, there are no reports on of the pPEO dependent on the film thicknesses.…”
Section: Introductionmentioning
confidence: 99%